Analysis of Enhanced Laser-Induced Breakdown Spectroscopy with Double Femtosecond Laser Pulses - 沈洁 杨正才 刘小亮 史彦超 赵培茜 孙少华 胡碧涛 (Plasma science & technology, 2015)
In this paper, an experimental study of collinear geometry double-pulse femtosecond LIBS was performed on a Ni sample in ambient air in an effort to clarify the contributing processes responsible for the signal enhancement observed in comparison with the single-pulse case. Doublepulse LIBS spectra show a very clear enhancement when an optimum inter-pulse delay was used. The influences of the inter-pulse delay between two pulses on the LIBS signal intensity, electron temperature and density were investigated. It is most remarkable that the evolutions of signal enhancement and electron temperature versus the inter-pulse delay showed the same behavior and revealed two main regimes of interaction. These results provide additional insight into the possible emission enhancement mechanisms in the double pulse configuration.